Transformational Leadership and Supply Chain Sustainability in Emerging Economies: The Serial Mediating Roles of Digital Capability and Green Innovation - Meisam Karami (SEISENSE Journal of Management, 2026)
Purpose: This study explores how transformational leadership drives supply chain sustainability through the sequential mediators of digital capability and green innovation among manufacturing SMEs in an emerging economy. It introduces Digital Green Orchestration Capability as a meta capability linking digital transformation and environmental performance.Design/Methodology: Using survey data from 332 manufacturing SMEs, the study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to test a serial mediation model grounded in Dynamic Capabilities Theory and Upper Echelons Theory.Findings: TL exerts no direct influence on SCS but shows full serial mediation via DC and GI. DGOC effectively converts leadership vision into sustainability outcomes through digital enablement and green implementation.Practical Implications: SME leaders should align digital transformation with sustainability strategies by investing in technological integration and eco-innovation routines.Originality: This research pioneers DGOC as a behavioral–capability mechanism bridging leadership cognition, digital transformation, and environmental sustainability in emerging economies.